Taiwan a success story - Shen, Cho-chun. (Taiwan : Kwang Hwa Mass Communications, 2005)
This program offers a brief introduction to the success story that is Taiwan which has experienced many conflicts, and has been ruled by the Dutch, the Chinese Qing Dynasty, and the Japanese. Since the Second World War, Taiwan has gradually moved towards greater stability.
Available in Chinese, English and French, Spanish, German, Japanese and Russian.
Keywords: Taiwan -- Economic condition; Taiwan -- Economuc policy